HUBUNGAN PENGETAHUAN IBU TENTANG TUMBUH KEMBANG DENGAN PERKEMBANGAN ANAK USIA 3-4 TAHUN DI KELOMPOK BERMAIN GOLDEN KIDS DI KECAMATAN TELANAI PURA KOTA JAMBI - Meri Kharisma; Nel Efni (Jurnal Akademika Baiturrahim Jambi, 2017)
Background: The development is the increased ability (skill) the structure and function of the body is more complex, in a regular pattern and can be predicted, as a result of the maturation process / maturity. There are four different aspects of child development, which consists of the development of fine motor, gross motor, language and socialization independence. To assess the four aspects of the child's development is by doing a screening test a child's development.Methods: This research is a quantitative research with cross sectional design aims to determine the relationship of mother's knowledge on of growth with the development of children aged 3-4 years in the Golden Kids Playgroup Telanai Pura District of the city of Jambi. This research has been conducted on the Golden Kids Playgroup Telanai Pura District of Jambi on 11-15 March 2016 with the instrument in the form of questionnaires, analyzed by univariate and bivariate using Chi-square test.Results: The results showed that maternal knowledge with the development of children aged 3-4 years in preschool Golden Kids can be from 39 high knowledge there were 18 (47.4%) the appropriate level of development, 17 (44.7%) of dubious level of development, and 3 (7.9 %) the deviation level of development of children aged 3-4 years in preschool Golden Kids. While the low knowledge of 19, 2 (10.5%) the appropriate level of development, 15 (78.9%) of dubious level of development and 2 (10.5%) the deviation level of development of children aged 3-4 years in the District Kids Playgroup Telanai Golden Temple City Jambi.Expected to health curriculum development, especially growth and development of children and mothers are also expected to increase awareness in stimulating growth and development of children so that children can go through the process optimal development.